A p-n heterojunction of CuI/TiO2 with enhanced photoelectrocatalytic activity for methanol electro-oxidation. (10th August 2017) - Sun, Mingjuan; Hu, Jiayue; Zhai, Chunyang; Zhu, Mingshan; Pan, Jianguo
Graphical abstract: Highlights: A p-n heterojunction of CuI/TiO2 is constructed. CuI/TiO2 is used as the support for depositing Pt nanoparticles. Enhanced catalytic activity of MOR by using Pt-CuI/TiO2 under light irradiation. Improved charger separation contributes to enhanced photoelectrocatalytic activity. Abstract: In this paper, a p-n heterojunction including p-type CuI and n-type TiO2 is first time constructed to be the support for the deposition of Pt. The as-prepared Pt-CuI/TiO2 modified electrode is studied for the electrocatalytic oxidation of methanol both in dark and under light illumination. Compare to traditional electrocatalytic oxidation, the electrocatalytic activity of Pt-CuI/TiO2 for methanol oxidation is improved with 4.0 times upon light illumination. Moreover, compare to bare CuI and TiO2 upon light illumination, the heterostructure of CuI/TiO2 displays 4.3 and 9.1 times enhanced electrocatalytic activity for methanol oxidation, respectively. The synergistic effects of photocatalysis and electrocatalysis as well as the effective charge transport in the p-n heterojunction of Pt-CuI/TiO2 contribute such big enhancement. The present studies indicate that the constructing of p-n heterojunction provides more insights in the fields of photoelectrochemical and photo–assisted fuel cell system.